Proportion and determinants of delay in diagnosis of pulmonary tuberculosis in a tertiary care centre of Gadag, Karnataka - Prabhunatti, Shivanand; Karinagannanavar, Aravind; Gaddeppanavar, Jagadish (International Journal Of Community Medicine And Public Health, 2020)
Background: In 1993, the World Health Organization (WHO) declared a state of global emergency for tuberculosis (TB), due to the steady increase of the disease worldwide. India is the highest TB burden country accounting for one fifth (21%) of the global incidence. Objectives were to study: 1) average delay in diagnosis of newly diagnosed pulmonary tuberculosis cases, 2) reasons for the delayed diagnosis of pulmonary tuberculosis patients and 3) extra cost incurred by the newly diagnosed pulmonary tuberculosis patients. Methods: An observational study was conducted from April 2017 to October 2017 using a non-probability purposive sampling. Delayed diagnosis is defined as the time interval between the onset of symptoms to the initiation of treatment after 16 days. The data was collected using a pretested semi-structured questionnaire. The performa included socio demographic profile of the study subjects, duration of delay in diagnosis, reasons for delay in diagnosis, direct and indirect cost incurred by the study subjects. Results: In present study we found that out of 66 patients majority of them found that for the first visit most of the patients preferred private hospitals (34.8%) followed by PHC (22.7%), district hospital (21.2%) CHC (13.6%) and the least was pharmacy (7.6%). Out of 66 patients, majority of the patients (63.6%) were diagnosed of pulmonary tuberculosis after their second visit. The main reasons were lack of awareness and lack of facilities in the peripheral health system. Conclusions: The mean patient delay was 13.13 days and the mean health care system delay was 25.3 days in diagnosing pulmonary tuberculosis.